2013
DOI: 10.1161/circimaging.112.000026
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Predictors of Reverse Remodeling After Cardiac Resynchronization Therapy and Subsequent Events

Abstract: Background-Studies of echocardiographic predictors of response after cardiac resynchronization therapy (CRT) have largely involved single parameters. We hypothesized that combining parameters would be more robust and sought to develop a multiparametric echocardiographic score for predicting CRT response. Methods and Results-Global longitudinal strain of left ventricle was added to standard echocardiographic measurements in 334 consecutive patients (224 men; mean, 65±12 years) who underwent baseline echocardiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 41 publications
2
42
0
Order By: Relevance
“…As well, the START score may be more useful compared to the MADIT score. The present results were consistent with a study that evaluated the usefulness of a multiparametric echocardiographic score method for CRT responders . In addition, we found that the START score was an independent predictor of clinical outcomes, which supports the finding in previous studies that patients with reverse remodeling have more‐favorable long‐term survival than those without reverse remodeling post‐RT …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As well, the START score may be more useful compared to the MADIT score. The present results were consistent with a study that evaluated the usefulness of a multiparametric echocardiographic score method for CRT responders . In addition, we found that the START score was an independent predictor of clinical outcomes, which supports the finding in previous studies that patients with reverse remodeling have more‐favorable long‐term survival than those without reverse remodeling post‐RT …”
Section: Discussionsupporting
confidence: 92%
“…Because the main subjects in the MADIT‐CRT study were patients classified as NYHA class I or II, it is unknown whether the MADIT scoring system can be used to make extrapolations in patients classified as NYHA class III or IV . Park et al reported that the echocardiographic score more accurately predicted LV reverse remodeling with CRT, and, compared to the MADIT score, it predicts clinical outcomes in 90% of patients classified as NYHA class III or IV. However, the echocardiographic score of these patients does not even include LBBB, which is the established clinical parameter.…”
Section: Discussionmentioning
confidence: 99%
“…115,116 In addition, in patients requiring CRT, an increase in GLS after implantation, in addition to the standard echocardiographic measurements, has been shown to predict responders and all-cause mortality at 1-year follow-up. 117 Although LV dyssynchrony is reported even in patients with HFpEF, 118,119 CRT has not been shown to result in any benefit when LVEF is >35% and, therefore, not recommended in these patients. 57 Instead, some studies have suggested that HFpEF patients often have interatrial dyssynchrony, which may contribute to their symptoms.…”
Section: Dyssynchronymentioning
confidence: 99%
“…Although several echocardiographic measurements, particularly involving tissue Doppler, have proven difficult outside major centers, the use of myocardial strain to document the site of maximal delay has now been shown in more than one randomized trial to benefit the outcome of cardiac resynchronization therapy (46,47). In addition, echocardiographic assessment of candidates for cardiac resynchronization therapy can predict nonresponse on the basis of nonsynchrony markers, including the severity of ventricular enlargement, RV involvement, and hemodynamic evaluation (48).…”
Section: Cardiac Resynchronization Therapymentioning
confidence: 99%